How do monetary policy announcements affect inflation expectations? - Kerstin Olsson (Uppsala University, Department of Economics, 2020)
This paper examines the effects of policy rate announcements on households' inflation expectations over the time period 2003-2015. The effect is estimated using a two-stage least squares regression model. The announced changes are instrumented by a monetary policy surprise variable obtained from high-frequency swap trade data. The effect of an announced increase in the policy rate on inflation expectations is significant and positive. According to the New-Keynesian model, the effect of an exogenous monetary policy shock depends on the assumptions made on the persistence of the shock process in the model. Alternatively, the results may be interpreted as the policy announcement signalling the central bank's private information on the direction of future inflation. Given the sizeable weight of housing costs in the Swedish CPI basket, the results may also be interpreted as reflecting the direct effect of interest rates on the CPI. In this case, households internalize the effects of interest rates on CPI, when forming expectations about the future rate of inflation.
urn:nbn:se:uu:diva-409534
Keywords: C26; E31; E52; G14; 330; Monetary policy; Inflationary expectations; Instrumental Variables; Event studies